The Effect of Organizational Climate, Work Discipline, and Achievement Motivation on the Performance of Public Elementary School Teachers in Binjai Kota District - Mardhani, Lies Eka; Dewi, Rosmala; Purba, Saut (Budapest International Research and Critics University, 2022)
This study aims to determine: (1) the influence of organizational climate on achievement motivation; (2) the effect of work discipline on achievement motivation; (3) the influence of organizational climate on productive teacher performance; (4) the effect of work discipline on productive teacher performance; and (5) the influence of achievement motivation on productive teacher performance. The research subjects were public elementary school teachers in Binjai Kota District with a total sample of 108 people. Sampling was done by proportionate simple random sampling. The research method is path analysis which aims to test theory and obtain information about research. Based on the hypothesis testing, it can be concluded: (1) there is a direct influence of organizational climate with achievement motivation expressed by ρ31> r table α = 5% (0.341> 0.159) and tcount> t table α = 5% (3.804> 1.645); (2) there is a direct effect of work discipline on achievement motivation expressed by ρ32> r table α = 5% (0.198> 0.159) and tcount> t table α = 5% (2,214> 1,645); (3) there is a direct influence of organizational climate on teacher performance expressed by ρ41> r table α = 5% (0.228> 0.159) and tcount> t table α = 5% (2.575> 1.645); (4) there is a direct effect of work discipline on teacher performance expressed by ρ42> r table α = 5% (0.184> 0.159) and tcount> t table α = 5% (2,160> 1,645); and (5) there is a direct effect of achievement motivation on teacher performance expressed by ρ43> rtabel α = 5% (0.335> 0.159) and tcount> ttable α = 5% (3.707> 1.645). The results of the study provide an overview of organizational climate, work discipline, and achievement motivation which affect teacher performance by 36.12% and the rest is determined by other conditions.